The Commonwealth Caribbean's African Diaspora: Culture and Management. Issue 1 (2nd January 2019) - Punnett, Betty Jane
ABSTRACT: Broadly, the African Diaspora includes anyone with roots in the African continent. The World Bank estimates that this is around 140 million people. This paper focuses on the diaspora in the English-speaking/Commonwealth Caribbean. It reviews existing research, both quantitative and qualitative, on culture and management, including recent results of the LEAD research. The paper provides a new and more complete understanding of the implications of culture for managers in these countries. The paper synthesizes the results from research projects to reach conclusions about practical implications for management. The paper also suggests avenues for future research.